PEMODELAN STRUKTUR BAWAH PERMUKAAN DAERAH SESAR JIWO KLATEN DENGAN METODE MEDAN MAGNET TOTAL - Irfan Roismanto; Tony Yulianto (Youngster Physics Journal, 2013)
This study, using the method of total magnetic field in the area of ​​Central Java Klaten, aims to interpret the subsurface structure of the fault zones surrounding Prambanan, Wedi, and Gantiwarno district that became the suspect of the aftershocks cause occurring on May 27, 2006. The total magnetic field measurements use GSM19T Series magnetometre with the accuracy of ± 0.5 nT which includes 158 points. From the interpretation result using the second vertical derivative analysis, it can be known that there are three fault areas which are categorised as normal faults. The first fault is found in the volcanic rocks composed by the layers of volcanic breccia, lava and tuff. It is characterised by a change in the susceptibility value from 0.3 to 0.2 cgs. The second section is in Kebo Butak rock formation comprising the layers of sandstone, clay, silt, and algomerat. It is characterised by changes on the susceptibility values from 0.126 to 0.007cgs and from 0.33 0.126 cgs. The last fault is located in the Semilir formation consisting of tuff rocks, pumice breccias and tuffaceous sandstone marked by changes on the susceptibility values ​​from 0.25 to 0.1 cgs and from 0.5 to 0.25 cgs. Keywords: jiwo fault, total magnetic field, klaten